UPAYA PEMERINTAH MEDORONG PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI WILAYAH KECAMATAN BONTANG BARAT - Andi Ilham (Jurnal Administrative Reform, 2017)
The community participation in development planning in the District of West Bontang not achieve optimal results or be able to support the accelerated development of the region. Yet the government's efforts to encourage community participation can bring changes to increase participation, but the changes are not fully participate in the community to support the accelerated development. It can be seen from the results of the discussion on sub focus research shows that community participation in terms of development planning has pretty good indication. It can be seen from his involvement in passing over the proposed program and discussion of proposed social programs in the field of economic activity, pengkatan quality of human resources and infrastructure activities has shown pretty good indication. Community participation in terms of the execution of the development has been pretty good indication. It can be seen from public involvement in implementing the program have been made in the work plan. and community participation in terms of development control, it is quite effective indication. It can be seen from public involvement in monitoring the activities in the field of economic relations, human resources and infrastructure, including quite effective.